(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2011)
The science of Environment studies is amulti-disciplinary science because it comprises various branches of studieslike chemistry, physics, medical science, life science, agriculture,public health, sanitary engineeringetc. It is the science of physical phenomena in the environment. It studies of the sources, reactions, transport, effect and fate of physical a biological species in the air, water and soil and the effect of from human activity upon these.